Prevalence and predictors of left atrial appendage inactivity in patients of rheumatic mitral stenosis in sinus rhythm: An observational study. Issue 11 (21st October 2021) - Mukhopadhyay, Saibal; Dwivedi, Yogesh; Yusuf, Jamal; Uppal, Abhimanyu; Mehta, Vimal
Abstract: Background: Systemic thromboembolism is a known complication of rheumatic mitral stenosis (RMS) in sinus rhythm (SR). Left atrial appendage (LAA), the commonest site of thrombus formation is usually hypocontractile (inactive) in such patients. We aimed to study the prevalence of LAA inactivity (LAAI) in severe RMS and assess its independent predictors. Methods: The study population consisted of 100 patients of severe RMS in SR. Transthoracic and transesophageal echocardiography were done to assess LAA contractile function. Patients with LAA‐peak emptying velocity < 25 cm/seconds were defined as having LAAI. Results: The mean age of study subjects was 31.66±8.69 years and 56% were females. 73% patients had LAAI (Group A), while remaining 27% had normal LAA function (Group B). Mitral‐valve area (MVA) and lateral annulus systolic velocity (Sa‐wave) were significantly lower while mitral valve mean gradient (MVMG) and serum fibrinogen were significantly higher (all p ‐values < 0.001) in group A patients. On multivariate binary logistic regression analysis, MVMG ( p < 0.001), Sa‐wave ( p = 0.02), and serum fibrinogen ( p = 0.005) were independent predictors of LAAI. Optimal cut‐off values of MVMG, Sa‐wave and serum fibrinogen for predicting LAAI were 11.5 mm Hg, 6.8 cm/seconds and 300 mg/dl, respectively. Sixty‐Seven (90.55%) patients in group A compared to 13(48.1%) in group B had LA/LAA smoke. LAAI was the only independent predictor of left atrium (LA)/LAA smoke with or without associated thrombus. Conclusion: There is high prevalence of LAAI in patients of severe MS in SR. MVMG, Sa‐wave, and serum fibrinogen levels are independent predictors of LAAI. LAAI is an independent predictor of LA/LAA smoke with or without associated thrombus.